PENGARUH MODEL PEMBELAJARAN PAIKEM BERBASIS MEDIA GRAFIS TERHADAP HASIL BELAJAR SISWA PADA PELAJARAN MATEMATIKA DI KELAS V SD NEGERI 068007 MEDAN TUNTUNGAN - Yoni Saragih; Patri Janson Silaban; Frida Simorangkir; Reflina Sinaga; Anton Sitepu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the effect of the PAIKEM learning model based on graphic media on student learning outcomes in mathematics lessons with data processing material in class V of SD Negeri 068007 Medan Tuntungan for the 2023/2024 academic year. This research was motivated by the low learning outcomes of students in class V of SD Negeri 068007 Medan Tuntungan which can be seen from the test scores. In this research, researchers used quantitative methods using experimental methods. The type of sample used in this research is saturated sampling. The research sample used was 22 class V students. Based on the research results, it shows that there is an influence of the PAIKEM learning model on student learning outcomes in mathematics subjects with data processing material for class V of SD Negeri 068007 Medan Tuntungan from testing the correlation coefficient of rcount (0.801) ≥ rtable (0.423) so it is concluded that the alternative hypothesis (Ha) accepted. Judging from the t test where tcount (7.774) ≥ttable (1.717), Ha is accepted. This shows that there is a significant positive influence between the PAIKEM learning model on student learning outcomes in mathematics subjects with data processing material in class V of SD Negeri 068007 Medan Tuntungan 2023/2024.